Early postoperative gait characteristics after unicompartmental knee arthroplasty: results and clinical implications - Xu Gu; Chengqiang Zhou; XinFei Zhu; Jie Cao; Hongwei Li (BMC Musculoskeletal Disorders)
Abstract Background and objective Despite the established efficacy of unicompartmental knee arthroplasty (UKA), quantitative assessments of early postoperative changes in gait and stability remain limited. This study investigated preoperative and postoperative alterations in gait and stability following UKA. Methods A cohort of 30 patients undergoing unilateral UKA at the Joint Surgery Department of the Affiliated Hospital of Xuzhou Medical University between May 2021 and 2022 was compared with a control group of 15 healthy elderly individuals without a history of hip or knee pathology. Evaluated parameters included Hospital for Special Surgery (HSS) scores, center of pressure path length, 95% confidence ellipse area, pace, stride length, stride frequency, gait cycle, and single support time percentage. Measurements were obtained preoperatively and at 1 and 3 months postoperatively for both groups. Results Step frequency remained unchanged between preoperative and 1-month postoperative assessments (p > 0.05). Stability declined at 1 month postoperatively relative to baseline, whereas other gait parameters showed significant improvement (p < 0.05). By 3 months, HSS scores and all gait and stability metrics exhibited substantial enhancement compared to baseline (p < 0.05). Conclusions Early gait recovery following UKA demonstrated a positive trajectory; however, step frequency showed minimal improvement, and stability remained compromised at 1 month postoperatively. Quantitative gait analysis provides a robust framework for monitoring rehabilitation progress after UKA.